2023
DOI: 10.3390/medicina59101732
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Barriers in Cranioplasty: 3D Printing in Low and Middle-Income Settings—Insights from Zenica, Bosnia and Herzegovina

Hakija Bečulić,
Denis Spahić,
Emir Begagić
et al.

Abstract: Background and Objectives: Cranial defects pose significant challenges in low and middle-income countries (LIMCs), necessitating innovative and cost-effective craniofacial reconstruction strategies. The purpose of this study was to present the Bosnia and Herzegovina model, showcasing the potential of a multidisciplinary team and 3D-based technologies, particularly PMMA implants, to address cranial defects in a resource-limited setting. Materials and Methods: An observational, non-experimental prospective inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…The use of AR in SB surgery is at a specific stage of development. On the one hand, there are obvious advantages that real-time 3D technology offers to surgeons in optimizing procedures related to SB surgery [14,[78][79][80]. On the other hand, this promising technology currently has its limitations, which are reflected in the current development of the equipment itself [81], the training of staff to use these new techniques [82], and the inaccessibility in less-developed countries or countries whose health systems are less able to follow the technological development of medical services [83].…”
Section: Discussionmentioning
confidence: 99%
“…The use of AR in SB surgery is at a specific stage of development. On the one hand, there are obvious advantages that real-time 3D technology offers to surgeons in optimizing procedures related to SB surgery [14,[78][79][80]. On the other hand, this promising technology currently has its limitations, which are reflected in the current development of the equipment itself [81], the training of staff to use these new techniques [82], and the inaccessibility in less-developed countries or countries whose health systems are less able to follow the technological development of medical services [83].…”
Section: Discussionmentioning
confidence: 99%
“…Bečulić et al reported the usefulness of preoperative planning with three-dimensional (3D) printing in surgical treatments for craniofacial reconstruction patients [ 11 ]. Advances in 3D imaging and printing can aid in more accurate and safer procedures for patients.…”
Section: Discussionmentioning
confidence: 99%